Effects of the loss and reconstruction of molar occlusal support on memory retrieval and hippocampal neuron density in rats. Issue 3 (July 2019) - Kurozumi, Akimasa; Hara, Tetsuya; Sakamoto, Shunichi; Araki, Daisuke; Iida-Tamada, Sachiyo; Kuroda-Ishimine, Chisa; Minagi, Shogo
Abstract: Purpose: Animal experiments have shown that the loss of occlusal support causes impairments in spatial cognition. Many reports have focused on the memory encoding process, and only few studies have investigated the effect on memory retrieval. This study aimed to examine the effects of both the loss and reconstruction of occlusal support on the memory retrieval process and on the number of hippocampal pyramidal cells. Methods: The experimental animals were divided into a molarless group, in which molars were extracted, a denture-wearing molarless group with experimental dentures inserted after molar extraction, and a control group. Radial maze trials were performed for 20 consecutive days (acquisition phase). The rats were tested on long-term memory retention following the acquisition phase in eight trials every five days, and in an additional trial 20 days later (probe phase). Results: The denture-wearing molarless group showed higher levels of spatial learning and memory than the molarless group. There were no significant differences in memory retrieval during the probe phase between the denture-wearing molarless and the control group. The molarless group showed significantly worse spatial learning and memory and had fewer neurons in the hippocampus than the control group. Conclusions: Our results suggest that the loss of occlusal support decreases the number of pyramidal cells in the hippocampus and impairs memory decoding and retrieval. However, this effect is suppressed by the reconstruction of occlusal support.